Advances in Cognitive Remediation Training in Schizophrenia: A Review - Brianna Fitapelli; Jean-Pierre Lindenmayer (Brain Sciences, 2022)
Cognitive Remediation Training (CRT) in schizophrenia has made great strides since its introduction in the 1990s. CRT was developed with the aim of improving the everyday functioning of individuals living with cognitive impairment. MEDLINE, PsychINFO, and Google Scholar were searched to extract peer-reviewed randomized controlled trials to produce the current review article. The aim of the present review is to summarize CRT effects on addressing cognitive changes in patients undergoing CRT as defined by the Cognitive Remediation Experts Workshop and to describe the areas of greatest impact in specific cognitive domains. Another area of this review aims to summarize the modalities of intervention (paper and pencil; computerized; home bound), the persistence of improvements, and their generalization to other domains of functioning. Finally, this review delineates barriers for wider dissemination of CRT, such as the transfer of research findings into clinical everyday practice and future developments of CRT.